Promoting Gender Affirmative Pedagogy in Italian Early Childhood Education and Care Services: Addressing the Needs of Trans and Gender Expansive Children - Alessia Ale* Santambrogio; Giuseppe Burgio (Zero-a-seis)
Increased visibility of trans and gender expansive children challenges Italian early childhood education and care services to provide welcoming and supporting educational environments. Drawing on national and international research, this article explores how cisnormativity and gender stereotypes can affect trans and gender expansive children within early childhood education and care settings. It proposes a framework that acknowledges the complexity of gender identity, and offers strategies for creating gender affirmative environments, drawing on a gender affirmative pedagogical approach. By embracing this approach, early childhood education and care services can empower trans and gender expansive children's developmental journeys, foster more welcoming and equitable educational environments, and promote gender health and social justice within the early childhood education system, and the broader Italian society alike.